The Impact of Online Reviews and Ratings on Consumer Purchasing Decisions on E-commerce Platforms - Rachmiani, Rachmiani; Kintan Oktadinna, Nabila; Rachmat Fauzan, Tribowo (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study aims to analyze the impact of online reviews (Online et al.) and product ratings on consumer purchasing decisions on e-commerce platforms. In the digital era, OCR and product ratings have become key elements in building consumer trust, reducing perceived risk, and influencing purchasing behaviour. This study uses a quantitative approach with an online survey as a data collection method, involving 180 respondents selected by purposive sampling. Respondents are active consumers on e-commerce platforms such as Tokopedia, Shopee, and Bukalapak, with the criteria of having a shopping experience at least once in the last six months. Data analysis used descriptive and inferential statistics, including Pearson correlation tests and linear regression, to identify the relationship between reviews, ratings, and purchasing decisions. The results showed that positive reviews significantly increase consumer trust (β = 0.52, p < 0.05), while negative reviews are stronger in building risk perceptions that reduce purchase intentions (β = -0.48, p < 0.05). In addition, product ratings play an important role as a quality signal; Highly rated products tend to increase consumer trust (r = 0.65, p < 0.05) and influence purchase decisions simultaneously with reviews, with a coefficient of determination of 0.62. This study confirms that product reviews and ratings are significant social proof in online shopping. These findings provide strategic implications for e-commerce players to encourage positive reviews, respond to negative reviews professionally, and improve product ratings through consistent quality. Thus, strategies focusing on managing reviews and ratings can improve product competitiveness in the competitive e-commerce market. This study also recommends further exploration of moderating variables such as brand image and service quality to understand consumer behaviour dynamics holistically.